Prevalence of blindness and visual impairment among yanomami Indigenous people in the Brazilian Amazon region: a cross-sectional observational study at CASAI-YResearch in context - Maria Christina Chagas Ferreira; Marcos Antonio Pellegrini; Bianca Jorge Sequeira (The Lancet Regional Health. Americas)
Summary: Background: Indigenous populations in the Americas experience significant health inequities, especially in remote areas. Among the Yanomami, a highly mobile Indigenous people living in the Amazon, ocular health data are scarce. This study aimed to estimate the prevalence and causes of visual impairment and blindness among the Yanomami, contributing to public health planning for isolated populations. Methods: A cross-sectional observational study was conducted between June and August 2024 at the Yanomami Indigenous Health House (CASAI-Y), in Boa Vista, Brazil. A total of 158 self-identified Yanomami individuals aged ≥5 years were evaluated through comprehensive eye exams including presenting visual acuity (PVA), best-corrected visual acuity (BCVA), autorefractometry, dynamic refractometry, tonometry, fundus photography, and slit-lamp examination. Visual impairment was classified according to the ICD-11 criteria. Findings: The prevalence of moderate or worse visual impairment and blindness based on PVA was 15.8%, decreasing to 8.2% with BCVA. Cataract and uncorrected refractive error were the leading causes of visual loss. Visual impairment was more frequent among men and individuals aged >40 years. Statistically significant improvements in visual acuity were achieved with refractive correction (p < 0.001). Cultural and logistical barriers were identified as major limitations to access. Interpretation: The high burden of preventable visual impairment in the Yanomami population underscores the need for accessible and culturally adapted eye care services. Corrective lenses and cataract surgery could substantially improve quality of life. Targeted strategies including mobile screening, Indigenous health agents and teleophthalmology should be prioritized to prevent avoidable blindness. Funding: No funding.